Optimization and characterization of bioethanol production from Icacina trichanta Oliv and Anchomanes difformis Blume as non-food starch feedstocks - Chizoma Nwakego Adewumi; Humphrey Nwenenda Dike; Ozioma Achugasim; Vincent E. Efeovbokhane; Adekunle Akanni Adeleke; Olabode Oluwasanmi; Hauwa Abubakar Rasheed; Damilola Deborah Olaniyan (Center of Biomass & Renewable Energy (CBIORE), 2026)
The growing competition between food and fuel remains the major drawback of first-generation bioethanol production. Despite their high conversion efficiencies and role as cleaner substitutes for fossil fuels, their cost implications in the production process have led to the search for utilization alternative non-food crops. This study investigates the use of two non-food starch crops, Anchomanes difformis Blume (ADB) and Icacina trichantha Oliv. (ITO), as sustainable alternatives to cassava (CAS) for bioethanol production. Enzymatic hydrolysis conditions were optimized using Response Surface Methodology (RSM), while the bioethanol was characterized by Fourier Transform Infrared Spectrophotometry (FTIR) and High-Performance Liquid Chromatography (HPLC). Results showed that optimum sugar yields were achieved at 180 Unit/g α-amylase and 480 Unit/g amyloglucosidase, where ITO, ADB, and CAS produced 74.29 g/L, 80.81 g/L, and 70.61 g/L reducing sugars, respectively. Correspondingly, ethanol yields were highest in ADB (34.08 g/L with 81.82% efficiency), followed by ITO (31.66 g/L with 84.04% efficiency) and CAS (30.38 g/L with 88.58%). Substrate inhibition was observed, indicating an inverse relationship between glucose concentration and ethanol conversion efficiency. The Michaelis–Menten model was employed to study the kinetics of the entire production process which demonstrated that ADB is the strongest performer overall (producing more ethanol per unit time). The study highlights that ADB and ITO, both non-edible and widely available in Nigeria, demonstrate superior sugar and ethanol yields compared to cassava, positioning them as promising candidates for sustainable, low-cost, and non-food feedstocks in bioethanol production. Their use can enhance energy security, reduce pressure on food crops, and contribute to climate change mitigation by providing renewable alternatives to fossil fuels.